The indirect verification of the going concern assumption by analysing the threat of bankruptcy - Michal Karas; Mária Režňáková (Management : Journal of Contemporary Management Issues, 2020)
The generally accepted aim of doing business is to maximize the business value. The value of a business strongly depends on its ability to generate future cash flow for its owners. A necessary condition is that the business remains financially viable or in other words, the business should meet the assumption of going concern principle. Verifying such an assumption, however, remains an issue. We suggest that this could be indirectly verified as an absence of threat of imminent financial distress. For this purpose, we analysed a set of cash flow and profit based ratios along with a set of other ratios with a potential influence on the business value. In terms of sample we focus on Czech manufacturing SMEs that were selected, due to their specific features resulting from the financial constraints. The F-test and t-test were employed as a method of identifying the typical signs of risk of financial distress or rather obstacles in accepting the going concern principle. We found that only four of the analysed ratios could serve effectively for this purpose. The best results were achieved when employing ratios describing the operational cash flow or short-term debt, where the gap between viable business and those with limited prospects is the widest.